ANALISIS PERAN ORANGTUA DALAM PERKEMBANGAN EMOSI ANAK - Mahmada Assyifa; Muhammad Yahya Maulida Fahmi; Nabilah Khoirrun Nisak; Nadia Dwi Insani; Najwa Salsabila Putri Purwagita; Surayanah Surayanah (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2026)
Emotional development in children is a crucial aspect that determines their future social intelligence and psychological well-being. Nevertheless, emotional regulation issues in children are still frequently encountered due to a lack of parenting synergy between the family and school environments. This study aims to analyze the roles and forms of collaboration between teachers and parents in supporting children's emotional development. The research method used is descriptive qualitative with a case study approach. The research stages include data collection through participatory observation at school, in-depth interviews with teachers and parents, and documentation study, which are then analyzed through the stages of data reduction, data display, and conclusion drawing. The results show that parents play a foundational role in laying the groundwork for a sense of security, providing affection, and acting as the primary role models for emotional regulation at home. Meanwhile, teachers act as facilitators who manage and train children's socio-emotional skills within the context of structured group dynamics at school. The main conclusion of this study is that children's emotional development will reach an optimal level when there is consistent two-way communication and alignment of guidance strategies between the school and the family. ABSTRAK Perkembangan emosi pada anak merupakan aspek krusial yang menentukan kecerdasan sosial dan kesejahteraan psikologis mereka di masa depan. Meskipun demikian, masih sering ditemukan masalah regulasi emosi pada anak akibat kurangnya sinergi pola asuh antara lingkungan keluarga dan sekolah. Penelitian ini bertujuan untuk menganalisis peran serta bentuk kolaborasi antara guru dan orang tua dalam mendukung perkembangan emosi anak. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan pendekatan studi kasus. Tahapan penelitian meliputi pengumpulan data melalui observasi partisipatif di sekolah, wawancara mendalam terhadap guru dan orang tua murid, serta studi dokumentasi, yang kemudian dianalisis melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa orang tua memegang peran fondasional sebagai peletak dasar rasa aman, pemberi afeksi, dan teladan utama regulasi emosi di rumah. Sementara itu, guru berperan sebagai fasilitator yang mengelola dan melatih keterampilan sosial-emosional anak dalam konteks dinamika kelompok yang terstruktur di sekolah. Simpulan utama dari penelitian ini adalah bahwa perkembangan emosi anak akan mencapai tingkat optimal ketika terdapat komunikasi dua arah yang konsisten serta keselarasan strategi pendampingan antara pihak sekolah dan keluarga.